Dynamics of Output and Employment in the U.S. Economy - Deepankar Basu; Duncan K. Foley (University of Massachusetts, Department of Economics, 2011)
This paper investigates the changing relationship between employment and real output in the U.S. economy from 1948 to 2010 both at the aggregate level and at some major industry-grouping levels of disaggregation. Real output is conventionally measured as value added corrected for price inflation, but there are some industries in which no independent measure of value added is possible and existing statistics depend on imputing value added to equal income. Indexes of output that exclude these imputations are closely correlated with employment over the whole period, and remain more closely correlated during the current business cycle. This analysis offers insights into deeper structural changes that have taken place in the U.S. economy over the past few decades in a context marked by the following three factors: (i) the service (especially the financial) sector has grown in importance, (ii) the economy has become more globalized, and (iii) the policy orientation has increasingly become neoliberal. We demonstrate an economically significant reduction in the coefficient relating employment growth to output growth over the business cycles since 1985. Some of this change is due to sectoral shifts toward services, but an important part of it reflects a reduction in the coefficient for the goods and material value-adding sectors. JEL Categories: E12, E20
Keywords: E12; E20; 330; Okun's Law; Kaldor-Verdoorn E_ect; Global restructuring; measurement of real output